Efficacy and safety of cold versus hot snare polypectomy for small (5–9 mm) colorectal polyps: a multicenter randomized controlled trial - de Benito Sanz, Marina; Hernández, Luis; Garcia Martinez, María Isabel; Diez-Redondo, Pilar; Joao Matias, Diana; Gonzalez-Santiago, Jesús M.; Ibáñez, Mercedes; Núñez Rodríguez, María Henar; Cimavilla, Marta; Tafur, Carla; Mata, Laura; Guardiola-Arévalo, Antonio; Feito, Jorge; García-Alonso, Francisco Javier; on behalf of the POLIPEC HOT-COLD Study Group (Endoscopy, 2021)
Background Resection techniques for small polyps include cold snare polypectomy (CSP) and hot snare polypectomy (HSP). This study compared CSP and HSP in 5–9 mm polyps in terms of complete resection and adverse events.Methods This was a multicenter, randomized trial conducted in seven Spanish centers between February and November 2019. Patients with ≥ 1 5–9 mm polyp were randomized to CSP or HSP, regardless of morphology or pit pattern. After polypectomy, two marginal biopsies were submitted to a pathologist who was blinded to polyp histology. Complete resection was defined as normal mucosa or burn artifacts in the biopsies. Abdominal pain was only assessed in patients without < 5 mm or > 9 mm polyps. Results 496 patients were randomized: 237 (394 polyps) to CSP and 259 (397 polyps) to HSP. Complete polypectomy rates were 92.5 % with CSP and 94.0 % with HSP (difference 1.5 %, 95 % confidence interval –1.9 % to 4.9 %). Intraprocedural bleeding occurred during three CSPs (0.8 %) and seven HSPs (1.8 %) (P = 0.34). One lesion per group (0.4 %) presented delayed hemorrhage. Post-colonoscopy abdominal pain presented similarly in both groups 1 hour after the procedure (CSP 18.8 % vs. HSP 18.4 %) but was higher in the HSP group after 5 hours (5.9 % vs. 16.5 %; P = 0.02). A higher proportion of patients were asymptomatic 24 hours after CSP than after HSP (97 % vs. 86.4 %; P = 0.01). Conclusions We observed no differences in complete resection and bleeding rates between CSP and HSP. CSP reduced the intensity and duration of post-colonoscopy abdominal pain.